Peran Perangkat Desa Dan Partisipasi Masyarakat Terhadap Akuntabilitas Pengelolaan Dana Desa : (Desa Bidar Alam Kecamatan Sangir Jujuan Kabupaten Solok Selatan) - Gerry Hamdani Putra; Frengki Iksa Novendri (Jurnal Kendali Akuntansi, 2024)
The purpose of this study is to examine the effect of the role of village apparatus and community participation on accountability of village fund management (Nagari Bidar Alam, Sangir Sangir Jujuan District, South Solok Regency). This type of study uses quantitative methods, data collection through the distribution of questionnaires to 40 respondents The sampling technique used is the Saturated Sampling Technique, which is a sampling technique when all members of the population are used as samples, using instrument test testing, (validity test and reliability test), classical assumption test (normality test, multicollinearity test and heteroscedasticity test) then multiple linear regression and test hypothetical with the help of SPSS application. The results of the study show that the role of village apparatus has a positive and significant effect on the accountability of village fund management, and community participation has a positive and significant effect on the accountability of village fund management.